2015
DOI: 10.1186/s12944-015-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum resistin levels correlate with psoriasis: a meta-analysis

Abstract: BackgroundRecent studies implicate adipokines in the pathogenesis of inflammatory diseases, including psoriasis. In this study we evaluated the significance of serum resistin levels in psoriasis patients using a meta-analysis approach.223MethodsRelevant articles were retrieved by searching the following English and Chinese databases: Cochrane Library, PubMed, Springer Link, Chinese Biomedical Database (CBM) and Chinese National Knowledge Infrastructure (CNKI). The retrieved studies were subjected to a thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Our study confirms the results of other meta-analyses that have been previously performed on the same topic [9][10][11]. Nevertheless, the novelty of the present metaanalysis consists of (i) inclusion of all 3 types of adipokines together, providing the most complete and comprehensive aspect of this key issue and (ii) analysis of more than double the number of studies compared to previous meta-analyses, making it an updated review in the field.…”
Section: First Authorsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study confirms the results of other meta-analyses that have been previously performed on the same topic [9][10][11]. Nevertheless, the novelty of the present metaanalysis consists of (i) inclusion of all 3 types of adipokines together, providing the most complete and comprehensive aspect of this key issue and (ii) analysis of more than double the number of studies compared to previous meta-analyses, making it an updated review in the field.…”
Section: First Authorsupporting
confidence: 89%
“…Recent studies suggest that adipokines, such as leptin, resistin, and adiponectin, may be implicated in the pathogenesis of psoriasis [9][10][11]. Both leptin and resistin are known to promote the production of proinflammatory mediators involved in the pathogenesis of psoriasis, such as TNF-α and CXCL8 [12].…”
mentioning
confidence: 99%
“…Conversely, in another study, both serum adiponectin and leptin levels were significantly decreased in psoriatic patients in comparison with the control group [58]. Other reports detected significantly lower levels of adiponectin and visfatin, and significantly higher levels of vaspin, omentin, chemerin, and resistin in psoriatic patients as compared to the control group [42, [59][60][61][62]. Of note, a meta-analysis including nine case-control studies, containing 421 psoriasis patients and 348 healthy controls, revealed a statistically significant association between serum resistin levels and psoriasis [59].…”
mentioning
confidence: 88%
“…Other reports detected significantly lower levels of adiponectin and visfatin, and significantly higher levels of vaspin, omentin, chemerin, and resistin in psoriatic patients as compared to the control group [42, [59][60][61][62]. Of note, a meta-analysis including nine case-control studies, containing 421 psoriasis patients and 348 healthy controls, revealed a statistically significant association between serum resistin levels and psoriasis [59]. Interestingly, successful treatment of psoriasis with biologicals (i.e., infliximab and ustekinumab) or phototherapy (narrow band-UVB) was related to an increase of adiponectin serum levels and a decrease of leptin and resistin serum concentration [60].…”
mentioning
confidence: 94%
“…Many studies reported that resistin was associated with insulin resistance, hyperglycemia and obesity (9)(10)(11). In addition, resistin was shown to be related with inflammation and immunity in many disorders including atherosclerosis, renal disorders, respiratory system disorders and psoriasis (11,12).…”
Section: Introductionmentioning
confidence: 99%